A conceptual flow field with metallic foam for enhanced performance and thermal management in a PEM fuel cell - Pouya Barnoon (Case Studies in Thermal Engineering)
The flow field configuration significantly influences the output power of PEMFCs. Common designs often result in lower current densities, making it challenging to achieve higher current density and better uniformity of reactant gases. This study introduces a conceptual flow field design on the cathode side to enhance power density and reactant gas uniformity. Two scenarios are analyzed: with and without metallic porous foam in the gas flow channels. The impact of each scenario on current density, power density, species distribution, and fuel cell temperature is investigated. Results show that metallic porous foam enhances power density and promotes uniform species consumption. It also plays a crucial role in managing fuel cell temperature. However, nanofluids do not outperform liquid water in cooling the fuel cell. The use of metallic porous foam results in a 10.93 % increase in power density compared to the clear region in the saturated state.